PREVALENCE OF THEILERIOSIS IN CATTLE IN KARNATAKA STATE - Roopa Satish; M. Narayana Bhat; Placid D’Souza (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Blood and sera samples collected from 258 animals of four different locations viz: Chinthamani Taluk, Veterinary Hospital, Yelahanka, Dairy Farm and Veterinary College Hospital, Hebbal examined by blood smear examination and Dot-ELISA to study the prevalence of theileriosis. The overall prevalence of theileriosis in the present study was found to be 26.74 per cent by blood smear examination and 55.81 per cent by Dot-ELISA. There was a significant difference in the results of blood smear examination and Dot-ELISA (P< 0.05). On blood smear examination, T. annulata organisms were predominantly of ring form. The prevalence of theileriosis Veterinary College Hospital, Hebbal was found to be 17.33 per cent by blood smear examination and 36 per cent by Dot-ELISA. At Veterinary Hospital, Yelahanka the prevalence of theileriosis was found to be 7.04 per cent by blood smear examination and 63.38 per cent by Dot-ELISA. College Dairy Farm, 13.33 per cent were positive by blood smear examination and 35.56 per cent were positive by Dot-ELISA. In Chintamani Taluk, the prevalence was found to be 67.16 per cent by blood smear examination and 83.58 per cent by Dot-ELISA.